2015
DOI: 10.3920/jiff2015.0029
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of willingness to eat insects in the USA and India

Abstract: One of the major, if not the major impediment to large scale increases of human insect consumption, is the strong rejection of insects as food by most of the world’s population. In an effort to understand this aversion, we surveyed online samples of adults living in the USA and India to participate in a study on ‘attitudes toward food’. A substantial proportion of both Americans (72%) and Indians (74%) were at least willing to consider eating some form of insect food. Men were more willing to try eating insect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
183
4
18

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 212 publications
(221 citation statements)
references
References 18 publications
16
183
4
18
Order By: Relevance
“…Consumers, familiar with edible insects accepted these processed insects readily and it facilitated commercialisation. It has also been suggested that gradually increasing concentrations of insects in flour might be effective (110) . This has been called the bottom-up approach, contrary to the top-down approach in which expensive restaurants have insects on the menu (see next point).…”
Section: Consumer Attitudesmentioning
confidence: 99%
See 4 more Smart Citations
“…Consumers, familiar with edible insects accepted these processed insects readily and it facilitated commercialisation. It has also been suggested that gradually increasing concentrations of insects in flour might be effective (110) . This has been called the bottom-up approach, contrary to the top-down approach in which expensive restaurants have insects on the menu (see next point).…”
Section: Consumer Attitudesmentioning
confidence: 99%
“…It is not primarily based on the sensory properties of potential foods, but rather on knowledge of the nature or history of a potential food. Interestingly, disgust has been identified as the main reason for persons totally rejecting insects as food (110) . It has been proposed to harness disgust as a positive feature of insects, what Rozin et al (111) called benign masochism.…”
Section: Consumer Attitudesmentioning
confidence: 99%
See 3 more Smart Citations